A theoretical study of the regio- and stereoselectivities of non-polar 1, 3-dipolar cycloaddition reaction between C-diethoxyphosphoryl-N-methylnitrone and N-(2-fluorophenyl)acrylamide. (3rd March 2016) - Chafaa, Fouad; Hellel, Djamila; Nacereddine, Abdelmalek Khorief; Djerourou, Abdelhafid
ABSTRACT: The 1, 3-dipolar cycloadditions (13DC) of C -diethoxyphosphoryl- N -methylnitrone and N-(2-fluorophenyl) acrylamide have been studied using density functional theory (DFT) calculations at B3LYP/6-31G(d) level of theory. Our calculations show that this 13DC reaction takes place with complete ortho regioselectivity with endo stereoselectivity, which favours kinetically the formation of the ortho – endo cycloadduct, in agreement with the experimental observations. The inclusion of solvent effects does not modify the gas-phase selectivities but slightly decreases the reactivity of the reagents. Analysis of the bond order and charge transfer at the transition states indicates that this 13DC reaction takes place via a one-step asynchronous mechanism. Analysis of the DFT global reactivity indices and the Parr functions of the reagents allow us to provide an explanation of the regioselectivity of this 13DC reaction. GRAPHICAL ABSTRACT: